Execution of Restitution for Child Victims of Criminal Acts (A Study at the Grobogan District Prosecutor’s Office) - Thesa Tamara Sanyoto; Abdul Rachmad Budiono; Fachrizal Afandi (YURISDIKSI : Jurnal Wacana Hukum dan Sains, 2025)
This study aims to analyze the regulatory framework and implementation of restitution enforcement for child victims of criminal acts, with specific emphasis on the authority of Public Prosecutors at the Grobogan District Prosecutor’s Office. Restitution is a fundamental right granted to victims under the Child Protection Law and Law Number 12 of 2022 concerning Sexual Violence Crimes, designed to restore the material and immaterial losses suffered by children due to criminal acts. The law establishes the perpetrator’s responsibility to provide restitution and allows substitute imprisonment when the payment obligation is not fulfilled. This research applies a socio-legal methodology by integrating normative legal analysis with empirical examination of how restitution is implemented in practice. Such an approach allows the researcher to assess the compatibility between legal norms and their actual enforcement in safeguarding child victims’ rights. The findings reveal persistent challenges in restitution execution, including complicated procedures for filing applications with the Witness and Victim Protection Agency (LPSK), strict evidentiary requirements, limited victim awareness, and the absence of detailed technical guidelines for asset seizure to guarantee payment. When perpetrators fail to compensate, state-funded compensation is necessary to uphold victim protection. Therefore, strengthening restorative justice principles, enhancing coordination among law enforcement institutions, and ensuring clearer execution mechanisms are essential to guarantee legal certainty and fulfillment of restitution rights within Indonesia’s criminal justice system.